1996
DOI: 10.1016/s0039-6109(05)70453-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Splenectomy

Abstract: Dramatic decreases in length of hospital stay and time to complete recovery with laparoscopic cholecystectomy have led to the development of more advanced laparoscopic procedures. The rationale, technique, and early results with laparoscopic splenectomy are described in this article. Laparoscopic splenectomy is a complex procedure with a real potential for significant operative bleeding, but it can be accomplished successfully in greater than 80% of selected patients with minimal blood loss. If successful, len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
1
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 9 publications
3
24
1
1
Order By: Relevance
“…This correlation had already been reported in the literature [6]. In contrast to other reports [8,12,14], splenic weight did not correlate either with operative time or with length of postoperative recovery.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This correlation had already been reported in the literature [6]. In contrast to other reports [8,12,14], splenic weight did not correlate either with operative time or with length of postoperative recovery.…”
Section: Discussionsupporting
confidence: 63%
“…Historically, the presence of splenomegaly was regarded as a contraindication to the laparoscopic approach. Several authors [2,8,11,12] have reported worse results with massive enlarged spleens by laparoscopy than with normal spleens. Longer operative times, more intraoperative blood loss, higher conversion rate to laparotomy, and longer postoperative hospital stay are cited as the primary disadvantages of LS for splenomegaly as compared with the same operation for normal-size spleens.…”
Section: Discussionmentioning
confidence: 99%
“…Results from our first 15 patients (Initial Group) and 5 patients undergoing uncomplicated, open operations (Open Group) from April 1993 to October 1995 have been briefly reviewed elsewhere [8]. Updated outcomes of these patients were compared to 35 patients (Recent Group) operated on after October 1995.…”
Section: Methodsmentioning
confidence: 99%
“…In 1996, Rege et al [17] reported 15 cases of laparoscopic splenectomy with a conversion rate of 33%; spleens requiring conversion had a mean weight of 797 g. More recently, several series of LS for splenomegaly have been described. In 1998, Targarona et al [18] reported a series of 74 consecutive LS and analyzed the impact of spleen size on the operative and immediate clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is believed that the volume of the spleen can be a relative or even an absolute contraindication to the laparoscopic procedure [17], recent improvements and refinements to the techniques of laparoscopy now allow the laparoscopic approach to be used in splenomegaly cases [16,22]. Preliminary data (eight cases) from our group [19] concerning the management of splenomegaly via the a laparoscopic approach showed that although LS required a longer operative time, it was associated with significantly fewer red blood cell transfusions and a faster and less complicated postoperative stay than open splenectomy.…”
mentioning
confidence: 99%